Состояние генофонда – формулировка критериев - Кордюм, В.А. (Биополимеры и клетка, 1993)
Для оценки состояния генофонда и прогноза его изменения необходима формулировка соответствующих критериев. Формулируются три следующие составляющие оценки состояния генофонда и прогноза его изменения во времени: 1) демографическая; 2) экологическая; 3) генетическая. В последней (непосредственное состояние генофонда) выделяются три критерия – балансовый мутационного айсберга и мутационной восприимчивости. Критерии, в свою очередь, разбиваются на подкритерии. На основании предложенного построения на примере Украины проводится детальный анализ состояния и прогноза развития генофонда населения Украины. Для оцінки стану генофонду та прогнозу його зміни необхідна формулювання відповідних критеріїв. Формулюються три наступні складові оцінки стану генофонду та прогнозу його зміни у часі: 1 ) демографічна ; 2 ) екологічна ; 3 ) генетична . В останній (безпосередньо стан генофонду ) вирізняються три критерії - балансовий мутаційного айсберга і мутаційної сприйняття . Критерії , в свою чергу , розбиваються на підкритерії . На основі запропонованої побудови на прикладі України проводиться детальний аналіз стану і прогнозу розвитку генофонду населення України . The concept of genofond initially arose in connection with tasks of selection in agriculture and foreseed preservation of rare and vanishing species as their single representatives. In recent days the question of human genofond preservation arose. However, the term of genofond concerning human has to have qualitatively another meaning-totality of genomes of all humans but not those separate persons. This requires special analysis and, as element of such general analysis, a prognosis of genofond state. For evaluation of genofond state and for prognosis of its change it is necessary to formulate suitable criteria. There three components of genofond state evaluation are formulated: 1) demographycal; 2) ecological; 3) genetical. In genetical component (genofond state per se) there three criteria are distinguished. These criteria are subdivided in subcriteria. 1. Balance criterium of genetical component with variants: 1.1. Mutationally equilibrated genofond state; 1.2. Mutationally nonequilibrated genofond state (1.2.1. – nonequilibrated mutation-accumulating state; 1.2.2.– nonequilibrated mutation-clearing state). 2. Mutational iceberg criterium, including: 2.1. The state of system, clearing genome from mutations; 2.2. The structure of mutational iceberg. 3. Criterium of mutational succeptibility: 3.1. The level of antimutational resistance; 3.2. The level of elevated mutational succeptibility; 3.3. The level of mutational self-start (self-moment). On the basis of offred construction it is performed the detailed analysis of Ukrainian population genofond state and of prognosis of its development. It is noted, that taking into account available (mostly indirect) data, anxious situation is forming and that the prognosis, as such, is giving no grounds for optimism.